THE EFFECT OF PREGNANCY EXERCISE ON THE SMOOTH DELIVERY OF THE SECOND STAGE OF CHILDBIRTH PROCESS IN EKA MEDIKA PRATAMA CLINIC, PUNGGING VILLAGE, MOJOSARI SUB-DISTRICT, MOJOKERTO DISTRICT - Titiek Idayanti; Siti Fithrotul Umami (Nurse and Health: Jurnal Keperawatan, 2018)
Background. In childbirth, there are several factors that can affect the smooth delivery of the second stage, one of which is influenced by straining factors that can be anticipated by doing pregnancy exercise, in which pregnancy exercise can affect the slow pace of the second stage of childbirth process.Objectives. The purpose of this study was to determine the effect of pregnancy exercise on the smooth delivery of the second stage of childbirth process in Eka Medika Pratama Clinic, Pungging Village, Mojosari Sub-District, Mojokerto District.Methods. The method used in this study is analytic with a case control approach using research instruments in the form of questionnaires and observation sheets with a check list. The sample is some of the mothers who do pregnancy exercise and do not do pregnancy exercise during pregnancy in Eka Medika Pratama Clinic, Pungging Village, Mojosari Sub-District, Mojokerto District.Results. The results of data collection were processed by chi-square statistical test (X²) with a significance level of α = 0.05. The results of the study showed a significant relationship between pregnancy exercise and the smoothness of the second stage of childbirth process with a value of P = 0.007.Conclusion. Most of the respondents who do pregnancy exercise undergo the second stage of childbirth process more quickly than mothers who are not doing pregnancy exercise. Suggestions given in the results of this study are expected midwives provide counseling to pregnant women about the importance of doing pregnancy exercise during pregnancy to facilitate the second stage of childbirth process. Keywords: Pregnancy exercise, smooth delivery, second stage of childbirth process